The Improving Community Spirituality Through "Majelis Taklim" Activities - Octaviana, Dila Rukmi; Ramadhani, Reza Aditya; Attamimi, Taufik Abdullah; Ahmad, Rizki Fauzia; Haq, Alsadika Ziaul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The objectives of this study are: (1) Knowing the activities of the "Majelis Taklim" in increasing the spirituality of the community of Mbangun Hamlet, Sukowinangun Village, Magetan (2) Knowing the supporting factors of increasing community spirituality through the Taklim Assembly activities in Mbangun Hamlet, Sukowinangun Village, Magetan, (3) Knowing the changes that occur in the community Mbangun Hamlet, Sukowinangun Village, Magetan after the "Majelis Taklim" was held. This research is field research that uses a descriptive qualitative approach with a type of phenomenological research and multisite study at the An-Nahdliyah Taklim Council and the Taklim Darussalam Council. The research location is in Mbangun Hamlet (RW 01) Sukowinangun Village, Magetan. Data collection techniques in this study include observation, interviews, and documentation. The research subjects in this study include the Chairman of RW 01 (Mbangun Hamlet), the Management of the Taklim Council, and Taklim Council Pilgrims. The results of this study include (1) Activities in the taklim tausiyah council and questions and answers, dhikr Asmaul Husna and guardian pilgrimage (2) Supporting factors for increasing community spirituality through the activities of the "Majelis Taklim" there are two, namely: internal factors namely the intention of each self individuals to study religious knowledge and external factors such as environmental and family encouragement, "Majelis Taklim" governance (3) Changes in society after the holding of the "Majelis Taklim" including mosque worshipers or mosque increases, community knowledge is increasingly developing, pilgrims' clothing becomes more Islamic, the social life of the community is more controlled.